2009
DOI: 10.1074/jbc.m109.017665
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin/p120 Catenin Association at Cell-Cell Contacts Occurs in Cholesterol-rich Membrane Domains and Is Required for RhoA Activation and Myogenesis

Abstract: p120 catenin is a major regulator of cadherin stability at cellcell contacts and a modulator of Rho GTPase activities. In C2C12 myoblasts, N-cadherin is stabilized at cell contacts through its association with cholesterol-rich membrane domains or lipid rafts (LR) and acts as an adhesion-activated receptor that activates RhoA, an event required for myogenesis induction. Here, we report that association of p120 catenin with N-cadherin at cell contacts occurs specifically in LR. We demonstrate that interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 40 publications
5
48
0
1
Order By: Relevance
“…7B), thus showing that flotillin 1 is associated with GM1-containing membrane microdomains. As previously shown (Causeret et al, 2005;Taulet et al, 2009), we also observed that GM1 patching induced the co-patching of Ncadherin-GFP with GM1 in luciferase shRNA C2C12 myoblasts. In contrast, N-cadherin-GFP co-patching with GM1 was impaired in cells in which flotillin 1 was knocked down (Fig.…”
Section: Flotillins Are Required For Cadherin Accumulation At Ccjs Ansupporting
confidence: 88%
See 1 more Smart Citation
“…7B), thus showing that flotillin 1 is associated with GM1-containing membrane microdomains. As previously shown (Causeret et al, 2005;Taulet et al, 2009), we also observed that GM1 patching induced the co-patching of Ncadherin-GFP with GM1 in luciferase shRNA C2C12 myoblasts. In contrast, N-cadherin-GFP co-patching with GM1 was impaired in cells in which flotillin 1 was knocked down (Fig.…”
Section: Flotillins Are Required For Cadherin Accumulation At Ccjs Ansupporting
confidence: 88%
“…We previously demonstrated that N-cadherin association with cholesterol-rich membrane microdomains results in its association with p120 catenin and its stabilization at CCJs (Causeret et al, 2005;Taulet et al, 2009). We thus assessed whether flotillin 1 knockdown affected p120 catenin interaction with N-and E-cadherin and found that this was the case in both mesenchymal C2C12 myoblasts and epithelial MCF-7 and HCT-116 cells ( Fig.…”
Section: Flotillins Are Required For Cadherin Accumulation At Ccjs Anmentioning
confidence: 99%
“…The complexing of the junctional proteins p120-catenin (p120ctn) and N-Cadherin at cell-cell contact sites was shown to occur in cholesterol rich membrane domains in mouse C2C12 cells (87). A similar observation was made in differentiated human colon adenocarcinoma HT-29 cells, in which the interaction of E-Cadherin with p120ctn preferentially takes place in lipid rafts.…”
Section: Functions Of Flotillins In Cell Migration and Adhesionmentioning
confidence: 66%
“…Because we compared proteins with the same overall backbone and cytoplasmic domain, this correlation might not apply for general comparisons across cadherin subtypes due to possible differences in their interactions with GTPases (Anastasiadis et al, 2000;Boulter et al, 2010). Ccadherin and E-cadherin activate Rac1 (Noren et al, 2003;Yap and Kovacs, 2003), but N-cadherin ligation triggers RhoA activation (Charrasse et al, 2002;Comunale et al, 2007;Marrs et al, 2009;Taulet et al, 2009). Whether the latter is due to low N-cadherin affinity and Rac1/RhoA antagonism (Boulter et al, 2010;Burridge and Doughman, 2006;Comunale et al, 2007;Wildenberg et al, 2006), or to differences in GTPase interactions with N-cadherin complexes (Anastasiadis et al, 2000) remains to be determined.…”
Section: Discussionmentioning
confidence: 99%